Public Relations Implemented in Islamic Philanthropic Organizations at LAZISNU - Martha, Zike; Hakim, Lukman; Ihsani, A. Fikri Amiruddin (Universitas Islam Negeri Madura, 2023)
Islamic philanthropic organizations have been the people’s choice to distribute Zakat, Infaq, and Shadaqah. However, only a few realize that public relations is essential to maintaining relationships with audiences. NU Care LAZISNU East Java implements a public relations strategy to maintain public trust. This study aimed to analyze the implementation of public relations concepts in the Islamic philanthropic institution of NU Care LAZISNU, East Java. NU Care LAZISNU East Java, with various excellent programs, tries to build and maintain public trust as an institution that collects people’s funds and carries out a humanitarian mission. Thus, this research wants to examine further characteristics of public relations in Islamic philanthropic institutions to get a positive branding image. The method used qualitative research through interview techniques, observation, and documentation from NU Care LAZISNU, Scientific and Practical Basics of Islamic Communication East Java. The theory used to analyze is relationship management. The study results show that implementing public relations in the Islamic philanthropic institution at NU Care LAZISNU, East Java, is based on ethics, credibility, openness, trust, involvement, and mutual benefit principles. It is because this institution’s policies, activities, and programs are closely related to Islamic teachings in the form of the implementation of Zakat, Infaq, and Shadaqah. The public relations strategies are institutional identity, community involvement, publications, and events.